1976
DOI: 10.1002/jsfa.2740270608
|View full text |Cite
|
Sign up to set email alerts
|

Identification of volatiles from extracted commercial tuna oil with a high docosahexaenoic acid content

Abstract: Steam-distilled volatiles from the extracted oil of cooked tuna fish were fractionated and identified by g.c.-ms. There were 64 compounds identified in the oxygenated fraction and 62 in the hydrocarbon fraction. The hydrocarbon fraction was found to have an unusually low odour threshold of 5.0 parts/lOg (in water) and 3.75 parts/lOg when a solvent correction factor was applied. As expected, the odour threshold of the oxygenated fraction was much lower (0.6 parts/lOg and 0.51 parts/lOg when corrected).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Although some eight‐ and nine‐carbon carbonyls have been reported in menhaden oil47 and tuna oil,18 the absence of eight‐ and nine‐carbon aclohols and carbonyls has been noted in salted‐dried white herring45 and fish oil 16. The absence of eight‐ and nine‐carbon alcohols and carbonyls has been reported in herring and blue whiting fish powders, although some of these volatiles (2‐octanone and nonanone) were produced in high quantities on heating the powders 43…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some eight‐ and nine‐carbon carbonyls have been reported in menhaden oil47 and tuna oil,18 the absence of eight‐ and nine‐carbon aclohols and carbonyls has been noted in salted‐dried white herring45 and fish oil 16. The absence of eight‐ and nine‐carbon alcohols and carbonyls has been reported in herring and blue whiting fish powders, although some of these volatiles (2‐octanone and nonanone) were produced in high quantities on heating the powders 43…”
Section: Discussionmentioning
confidence: 99%
“…Although the flavour of fish has been examined extensively,3, 9–13 data on the volatiles of marine oils are scarce, apart from some on herring oil,14 menhaden oil,15, 16 cod liver oil17 and tuna oil 18. No data are available regarding the volatiles of marine meals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Alkylthiophenes have been identified in several meats, including fried and roast chicken, 25,26 and have also been found in turkey, but only in animals fed a tuna oil-supplemented diet. 10 The relatively mild cooking conditions used in the present study (surface temperature, 100°C) may possibly be responsible for the apparent absence of other sulphur-containing compounds of the type identified in the more extensively investigated volatiles of chicken. …”
Section: Volatile Compounds In Freshly Cooked and Stored Cooked Turkementioning
confidence: 92%
“…Because of the high content of oxidatively labile phospholipids in the muscle, 7 cooked turkey meat has been shown to be more susceptible to lipid oxidation than meat from other species, 8,9 and compounds derived from this process are the dominant components of cooked turkey volatiles. Crawford and Kretsch 10 identified 200 compounds in roast turkey distillates, with the majority (60%) occurring only in meat from birds fed a tuna oil diet, which produced a range of volatiles associated with fishy off-flavours. Reuneger et al 11 reported correlations between the levels of an unidentified compound, heptanal and 3,6-nonadienal and sensory scores for oxidized off-flavours in cooked turkey.…”
Section: Introductionmentioning
confidence: 99%